Psychosocial Aspects of Orthodontic Treatment Among Adolescents: A Systematic Review - Widya Kusumadewy; Miesje Karmiati Purwanegara (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Orthodontic treatment aims not only to improve the patient's occlusion but also to provide an attractive physical appearance. Orthodontic treatment can be started in adolescence in certain cases. Adolescence is a phase of self-identity development where physical appearance plays an important role. Therefore, the patient's age must be considered because it is related to psychosocial factors that will determine the success of orthodontic treatment. This paper aims to provide an overview of the psychosocial factors influencing orthodontic treatment in adolescents, particularly regarding their desire to undergo orthodontic treatment. Review: This review was conducted using electronic databases, including PubMed, EBSCOhost, and Scopus. The included studies focused on psychosocial factors considered in orthodontic treatment among adolescents. Relevant articles were selected and analyzed to identify psychosocial factors influencing orthodontic treatment in adolescents. Articles that meet the inclusion criteria are 7 articles on psychosocial impact, emotional well-being, self-esteem, motivation, and the patient's desire to undergo orthodontic treatment Conclusion: Psychosocial aspects such as self-esteem and social influence, including social media, have an important role in motivating adolescents to undergo orthodontic treatment. Orthodontists need to understand a person's emotional and cognitive development because it affects how a person receives orthodontic treatment. Communication and using appropriate approaches by considering psychosocial factors will improve the success of orthodontic treatment.